The scope of Baker's law. Issue 3 (20th July 2015) - Pannell, John R.; Auld, Josh R.; Brandvain, Yaniv; Burd, Martin; Busch, Jeremiah W.; Cheptou, Pierre‐Olivier; Conner, Jeffrey K.; Goldberg, Emma E.; Grant, Alannie‐Grace; Grossenbacher, Dena L.; Hovick, Stephen M.; Igic, Boris; et al.
<x xml:space="preserve">Abstract</x> <table-wrap position="anchor" orientation="portrait"> 656 I. I. 657 II. II. 658 III. III. 660 IV. IV. 661 V. V. 663 VI. VI. 663 VII. VII. 664 VIII. VIII. 664 665 References 665 </table-wrap> Summary Baker's law refers to the tendency for species that establish on islands by long‐distance dispersal to show an increased capacity for self‐fertilization because of the advantage of self‐compatibility when colonizing new habitat. Despite its intuitive appeal and broad empirical support, it has received substantial criticism over the years since it was proclaimed in the 1950s, not least because it seemed to be contradicted by the high frequency of dioecy on islands. Recent theoretical work has again questioned the generality and scope of Baker's law. Here, we attempt to discern where the idea is useful to apply and where it is not. We conclude that several of the perceived problems with Baker's law fall away when a narrower perspective is adopted on how it should be circumscribed. We emphasize that Baker's law should be read in terms of an enrichment of a capacity for uniparental reproduction in colonizing situations, rather than of high selfing rates. We suggest that Baker's law might be tested in four different contexts, which set the breadth of its scope: the colonization of oceanic islands, metapopulation dynamics with recurrent colonization, range expansions with recurrent colonization, and colonization through species invasions.